Synthesis of a Plant-based Dust Suppressant and Testing on Coal from Moatize, Mozambique - Campos, V. [UNESP]; Morais, L. C. [UNESP]; Mafavisse, I. M. (Croatian Society of Chemical Engineers/HDKI, 2022)
The dust suppressant was synthesized using Pinus elliottii resin as raw material for the new plant-based formulation. The dust suppressant formulation was prepared by solubilizing rosin in a ternary solution containing calcium chloride, ultrapure water, and ethanol in a molar ratio of 1:2:8. After centrifugation the supernatant was collected, 20 mL of 2 % γ-polyglutamic acid dissolved in an aqueous ethanol solution was added, and the mixture was stirred for 2 hours. The dust suppressant formulation included Pinus extract and γ-PGA acid, resulting in a plant-based dust suppressant. The performance of the new formulation in reducing PM10 was significantly superior (82.7 %) to that of water. This suppressant is suitable for spraying onto coal ore piles and hopper cars carrying coal ore. The wettability of the product was analyzed by the Walker test, which confirmed its adhesiveness to coal dust.
Keywords: coal; dust suppressant; Moatize; particulate matter; Pinus extract; γ-polyglutamic acid